Audit Committee and Audit Delay - Rai Ayu Santika Puspa Dewi; Ni Made Sunarsih; Ni Wayan Rustiarini (Faculty of Economics and Business, Universitas Warmadewa, 2024)
Every public company is obligated to submit audited financial reports on time. However, several companies could not publish the report within the specified period (audit delay). This study investigates the role of audit committee characteristics on audit delay. Audit committee characteristics are reviewed from 5 variables, namely member size, educational background, gender, meeting number, and tenure on audit delay. The study was conducted at manufacturing companies listed on the Indonesian Stock Exchange for three years, namely 2019-2021. The analysis technique uses multiple linear regression. The results of statistical tests found that the number of audit committees and female audit committees was proven to reduce audit delays. However, educational background in accounting and business, number of meetings, and tenure do not affect audit delay.